2021
DOI: 10.17159/2221-4070/2021/v10i2a7
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Experiences in the Implementation of the Life Skills CAPS for Learners With Severe Intellectual Disability

Abstract: This article focuses on a participatory process where the experiences of teachers regarding the implementation of the life skills curriculum and assessment policy statement (CAPS) for learners with severe intellectual disabilities (SID) in schools for learners with special educational needs were investigated. This curriculum for learners with SID has been developed to be more effective in meeting the needs of these learners. The curriculum ensures that learners can meet the requirements of the national CAPS us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…According to the participants, using workbooks is crucial as without it, extensive research, planning and time is required. This finding aligns with the research conducted by Rens and Louw ( 2021 ) on teachers’ experiences in implementing the Life Skills CAPS curriculum for learners with SID in both well-resourced and under-resourced schools in the North West province of South Africa. They concluded that the lack of specialised books, particularly for the SID curriculum, hinders implementation and poses a significant problem for teachers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…According to the participants, using workbooks is crucial as without it, extensive research, planning and time is required. This finding aligns with the research conducted by Rens and Louw ( 2021 ) on teachers’ experiences in implementing the Life Skills CAPS curriculum for learners with SID in both well-resourced and under-resourced schools in the North West province of South Africa. They concluded that the lack of specialised books, particularly for the SID curriculum, hinders implementation and poses a significant problem for teachers.…”
Section: Discussionsupporting
confidence: 90%
“…Following the establishment of democracy in 1994, the new government recognised the need to transform South Africa’s education system and address the discriminatory practices that had excluded individuals with severe disabilities (Rens & Louw 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…At its core, inclusive education provides equal opportunities for every student to learn and succeed in the school environment [3,4]. However, inclusive education is not only about placing learners with disabilities in ordinary public schools [5]. Inclusive education involves considering key aspects of education, including assessment practices, equitable access pathways, comprehensive support mechanisms, adequate resource allocation, effective leadership approaches, and clear policies.…”
Section: Introductionmentioning
confidence: 99%